First cycle experience of a business process re-engineering programme at Shabanie Mine. - Musingwini, C.; Muzoriwa, C.; Phuti, D.; Mbirikira, D. (The Southern African Institute of Mining and Metallurgy., 2005)
In the past ten to fifteen years, many organizations have applied business process re-engineering (BPR) to significantly improve their business competitiveness or stave off closures. The mining industry in Southern Africa is no exception and documented examples can be drawn from South Africa. Although the concept is superficially simple, its application has been marked by a high failure rate of about 70 per cent because it has been generally misunderstood. Shabanie mine, a chrysotile asbestos fibre producer in Zimbabwe took cognisance of this fact by cautiously embarking on a modular BPR programme in October of 2002. A year was used as a complete cycle or module for re-evaluation of the programme. Shabanie mine adopted BPR as part of management efforts to remain competitive amid serious threats to operational viability. These threats included hyper-inflation driven rising production costs, a declining world asbestos market and a possibility that Russia could take over the shrinking world asbestos market by dumping low-priced asbestos fibre. The only competitive advantage that the mine had was the high quality of its long-fibre chrysotile asbestos. The major BPR thrust was therefore to redesign processes for improved productivity and ultimately achieve a lower cost per ton of final asbestos fibre product. In addition, corporate culture change and cost-saving were also factored into the programme. This paper discusses the implementation experience of the BPR programme at the mine. The main BPR beneficial highlights are improved productivity, sizeable cost-savings, positive corporate culture change and identification of secondary projects. One of the lessons learnt from this programme is that mining companies will have to deal with the HIV/AIDS pandemic if they are to sustain high levels of productivity into the future.
Keywords: Shabanie Mine; Business process re-engineering (BPR); Magnesium printing plates; Asbestos; Cost effectiveness; Marketing; Productivity; Social aspects; Radical redesign